Koncepcja edukacji uniwersyteckiej Johna Henry’ego Newmana - Taylor, Sarah (Biuletyn Historii Wychowania, 2023)
The functioning of today’s universities has been influenced by centuries of changing educational concepts. The aim of the article is to describe and examine one of them – the concept of university education by John Henry Newman, which was created in the second half of the 19th century. Newman described his educational ideal, which he wanted to put into practice while being rector of the Catholic University of Ireland in Dublin. He stated that the function of the university must be broad, it should include both practical studying and learning universal knowledge as well as the comprehensive development of students. Newman built this concept on the basis of personal beliefs, his Christian faith and ties with the Catholic and Anglican churches and experiences from studying at the University of Oxford. The article analyses the works of Newman and explores the foundations of his educational concept.